Preparation of MOFs and MOFs derived materials and their catalytic application in air pollution: A review - He, Hanbing; Li, Ren; Yang, Zhihui; Chai, Liyuan; Jin, Linfeng; Alhassan, Sikpaam Issaka; Ren, Lili; Wang, Haiying; Huang, Lei (Catalysis today, 2021)
[Display omitted] •MOFs were used as catalysts in different applications of air pollution.•MOFs were modified to enhance catalytic performance in different ways.•Different kinds of materials were prepared by using MOFs as precursors or composites.•MOFs are promising materials in the field of gas-phase catalysis. Metal-organic framework (MOFs) composites are new kind of porous materials, with great specific surface area and extremely high porosity. MOFs have been in the catalytic application due to excellent catalytic properties such as, their unique structure and dispersed active centers. Hence, the chemical, environment and energy-related fields disciplines have made substantial applications of MOFs and its composites. Moreover, several researchers have made conducted extensive studies regarding the application of MOFs materials for air pollution control such as, including functionalization, loading, carbonization, oxidation of MOFs materials, and application of MOFs as sensors for air pollution monitoring. This review article is aimed at providing precise information about the efforts made by some researchers in the field of MOFs and MOFs derived materials and their application in other disciplines. The following areas have been succinctly reviewed: (1) general introduction of MOFs materials, (2) synthesis of various MOFs materials, composites and their derivatives, (3) catalysis of MOFs materials, composites and their derivatives on different air pollution, (4) summary and future prospects. We hope this review will help researchers understand more about the research progress of MOFs materials in the catalysis of air pollution.